Do Tax Planning, Deferred Tax, and CSR Influence Earnings Management? Evidence from Indonesian Financial Sector (2021–2023) - Nilam Kesuma; Silvia Marshanda Fernandez; Rela Sari; Daniel Petrov (PT. Altaf Publishing Corp, 2026)
This study aims to analyze the effect of tax planning, deferred tax burden, and Corporate Social Responsibility (CSR) on earnings management in financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The study population comprised 108 companies. The sample selection technique used was a purposive sampling method, resulting in a total sample of 69 companies that met the criteria. The data used were secondary data from company annual reports that included CSR disclosures, and data collection was carried out using the documentation method. Data analysis used SPSS version 30 software. The results showed that the variables of tax planning, deferred tax burden, and CSR did not affect earnings management, but simultaneously did not affect earnings management.